Perbandingan Abnormal Return Saham Sebelum dan Sesudah Perubahan Waktu Perdagangan Selama Pandemi Covid-19 - Deasy Lestary Kusnandar; Vivi Indah Bintari (Jurnal Pasar Modal dan Bisnis, 2020)
This study aims to determine the differences in abnormal returns before and after the announcement of changes in trading time on exchange transactions on the Indonesia Stock Exchange during the pandemic covid-19. The research population is all companies that entered into LQ45 companies on the Stock Exchange in the period February - July 2020, namely as many as 45 companies. The sample in this study was taken using the census method, meaning that the number of samples taken was equal to the number of members of the population. To test the hypothesis of this study using a paired sample test. This test is used to determine whether there is an average difference between two groups of pairs that are paired (related). That is, a sample but underwent two different treatments. The object of this research is abnormal return. To calculate abnormal returns, one must first find the actual return and expected return. To calculate the expected return using Market Adjusted Model measurements. The results of this study indicate that there are differences in abnormal returns before and after the announcement of changes in trading time for stock exchange transactions on the Indonesia Stock Exchange during the pandemic covid-19.